Sensitivity and specificity of fine needle aspiration cytological report in thyroid nodule at Her Royal Highness Princess Maha Chakri Sirindhorn Medical Center - Trongwongsa, Therdkait; Achintharangkoon, Panut (Journal of Medicine and Health Sciences, 2022)
Abstract Thyroid nodules may be investigated by various tests. Fine needle aspiration is one such test, which is easy, convenient, safe, fast, and effective. However, the cytology results are based on the method of obtaining specimens and the expertise of the pathologist. Therefore, the predictive value of cancer by FNA cytological reports from each hospital may vary from the Bethesda system for reporting cytopathology (BSRTC). For this reason, this study aimed to compare the sensitivity, specificity, accuracy and the positive predictive value of cytological reports in Her Royal Highness Princess Maha Chakri Sirindhorn Medical Center (MSMC) with BSRTC. A retrospective and diagnostic testing of all patients with thyroid nodules with FNA cytological reports in MSMC were conducted. The samples consisted of 133 patients and the information was collected at MSMC between October 1, 2012 and September 30, 2018. The factors included age, gender, cytological reports on fine needle aspiration and surgical pathology from excision. The sensitivity, specificity and diagnostic accuracy were 71.9%, 96.4% and 95%, respectively. The positive predictive value was 62.2%. These parameters were standard and close to that of other studies.